Pulsed Corona Discharge for Degradation of Methylene Blue in Water - Magureanu, Monica; Bradu, Corina; Piroi, Daniela; Mandache, Nicolae Bogdan; Parvulescu, Vasile (Plasma chemistry and plasma processing, 2013)
A pulsed corona discharge in multiwire-plate geometry, generated above water was studied for the removal of organic compounds in liquids. The degradation of methylene blue (MB) and the formation of hydrogen peroxide (H 2 O 2 ) were investigated. The MB solution was rapidly decolorized, evidencing the degradation of the dye after approximately 10 min plasma treatment. Nitrate, formate, sulphate and chlorine ions have been detected in the treated solution, explaining partly the change in the solution properties with plasma exposure, i.e. increase of electrical conductivity and decrease of pH. It was found that the concentration of H 2 O 2 generated in water increased with plasma exposure time, reaching 200 mg/L after 30 min treatment. In the MB solution less hydrogen peroxide was detected, suggesting reactions with the dye and its degradation products. The addition of FeCl 2 catalyst had a slight favorable effect on methylene blue degradation due to Fenton’s reaction. It was observed that MB and H 2 O 2 concentrations continue to decrease after the plasma treatment was stopped, suggesting that active species which accumulate in the solution may react post-plasma with methylene blue and its degradation products.